Three-dimensional vs standard laparoscopy: comparative assessment using a validated program for laparoscopic urologic skills - Cicione, A (2014)
OBJECTIVE: To compare the last generation of 3-dimensional imaging (3D) vs standard 2-dimensional imaging (2D) laparoscopy. MATERIALS AND METHODS: A prospective observational study was conducted during the 4th Minimally Invasive Urological Surgical Week Course held in Braga (Portugal) in April 2013. The course participants and faculty were asked to perform standardized tasks in the dry laboratory setting and randomly assigned into 2 study groups; one starting with 3D, the other with 2D laparoscopy. The 5 tasks of the European Training in Basic Laparoscopic Urological Skills were performed. Time to complete each task and errors made were recorded and analyzed. An end-of-study questionnaire was filled by the participants. RESULTS: Ten laparoscopic experts and 23 laparoscopy-naïve residents were included. Overall, a significantly better performance was obtained using 3D in terms of time (1115 seconds, interquartile range [IQR] 596-1469 vs 1299 seconds, IQR 620-1723; P = .027) and number of errors (2, IQR 1-3 vs 3, IQR 2-5.5; P = .001). However, the experts were faster only in the "peg transfer" task when using the 3D, whereas naïves improved their performance in 3 of the 5 tasks. A linear correlation between level of experience and performance was found. Three-dimensional imaging was perceived as "easier" by a third of the laparoscopy-naïve participants (P = .027). CONCLUSION: Three-dimensional imaging seems to facilitate surgical performance of urologic surgeons without laparoscopic background in the dry laboratory setting. The advantage provided by 3D for those with previous laparoscopic experience remains to be demonstrated. Further studies are needed to determine the actual advantage of 3D over standard 2D laparoscopy in the clinical setting.